Development of ISO 9001-compliant quality assurance model for residential building construction in South Africa - Hlatshwayo, Thokozani; Daniyan, Ilesanmi; Ramdass, Kemlall; Phuluwa, Humbulani Simon; Adeodu, Adefemi (Edelweiss Applied Science and Technology, 2025)
The imperative to enhance quality standards in South Africa's residential construction sector remains urgent, particularly given persistent quality lapses and rising stakeholder expectations. This study proposes a comprehensive ISO 9001-compliant quality assurance (QA) model tailored to residential building projects in South Africa. Using the Fishbone (Ishikawa) diagram for root cause analysis, six major quality determinants—human factors, technological tools, design and planning, regulatory compliance, project management, and material resources—are systematically examined. These elements are aligned with core ISO 9001 principles: customer focus, leadership, engagement of people, process approach, evidence-based decision-making, relationship management, and continual improvement. The model operationalizes QA/QC across all project phases—pre-design, design, construction, and post-handover—ensuring a lifecycle quality management strategy. Evidence indicates that skills development, effective stakeholder collaboration, and stringent regulatory oversight significantly improve construction outcomes. The study contributes a structured, principle-based QA model capable of addressing entrenched quality failures in the South African context, offering a replicable framework for broader application across emerging economies facing similar construction quality challenges.